Temperature and solar radiation utilization of rice for yield formation with different mechanized planting methods in the lower reaches of the Yangtze River, China - Zhi-peng XING; Pei WU; Ming ZHU; Hai-jun QIAN; Ya-jie HU; Bao-wei GUO; Hai-yan WEI; Ke XU; Zhong-yang HUO; Qi-gen DAI; Hong-cheng ZHANG (Journal of Integrative Agriculture)
Several studies have demonstrated the effect of planting methods on rice yield, but information on the climate resources is limited. This study aims to reveal the effects of planting methods on climate resources associated with rice yield in a rice-wheat rotation system in the lower reaches of the Yangtze River, China. Field experiments were conducted in 2014 and 2015 with two japonica, two indica hybrid, and two japonica-indica hybrid varieties grown under three mechanized planting methods: carpet seedling of mechanical transplanting (CT), mechanical direct seeding (DS), and pot-hole seedling of mechanical transplanting (PT). The rice yield and total dry matter under PT were greater than those under CT and DS methods. Besides, the entire growth duration and daily production showed significant positive relations with rice yield. Compared with CT and DS, the effective accumulated temperature and cumulative solar radiation of rice under PT were higher in phenological phases. In addition, the dry matter/effective accumulated temperature and solar energy utilization of rice under CT and DS were higher during vegetative phase and lower during reproductive and grain filling phases in contrast to PT. The mean daily temperature and mean daily solar radiation in the entire growth duration showed significant positive correlation with rice yield, total dry matter, and harvest index. This study demonstrated that when the mean daily temperature is <25.1°C in vegetative phase and >20.1°C in grain filling phase, rice yield could be increased by selecting mechanized planting methods. Most varieties under PT method exhibited high yield and climate resources use efficiency compared with CT and DS. In conclusion, the PT method could be a better cultivation measure for high rice yield, accompanied with high temperature and solar radiation use efficiency in a rice-wheat rotation system in the lower reaches of the Yangtze River, China.